Social Deviation Reflected In Saman Novel (1998) By Ayu Utami:A Sociological Approach - Ratnawati, Emy; , Drs. Abdillah Nugroho, M. Hum; , Nur Hidayat, M.Pd (2014)
This research is proposed to analyze how the social deviation is reflected in Saman Novel (1998) by Sociological Approach. There are two objectives: the first is to analyze the structural elements of the novel by finding character and characterization, setting, point of view, plot, style and theme, and the second is to analyze the novel based on sociological perspective by identifying the relationship between the novel and the social background of Indonesian society. This study uses qualitative method in which the data are taken from both primary and secondary data source in form of words, sentence and phrases. Primary data source is the Saman novel by Ayu Utami, while secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data researcher employs descriptive analysis. Based on the analysis, the researcher draws some conclusions as follows. First, there is a close relationship between the novel, Saman novel and the Indonesia social realities in the twentieth century. Second, Ayu Utami gives emphasis on the social deviation in Indonesia in the twentieth century. Third, the social realities of Indonesia contribute the creation of characters and characterization, setting, plot, and theme of the story.